Public education and student movements: the Chilean rebellion under a neoliberal experiment. Issue 4 (19th May 2019) - Inzunza, Jorge; Assael, Jenny; Cornejo, Rodrigo; Redondo, Jesus
Abstract: Chile is recognized in the educational policy field as one of the first laboratories of neoliberal initiatives. These policies, initiated under the dictatorship of Augusto Pinochet, did not change with the new democratic governments after 1990. This characteristic led international organizations to promote the Chilean policies in different contexts in Latin America and beyond. In 2006, a high school student movement occupied public and private schools, demystifying the outcomes of these policies. A new wave of demonstrations took place in 2011, with a college student leadership that paralyzed a significant amount of universities and schools throughout the country. After both waves of mobilizations, the political system opened the process of policy-making that considered the demands of social movements. In this article, we explore the dynamics between educational policies and social student movements in Chile, and the possibilities of change in favor of public education.